«ШӘРИЯР» ДӘСТАНЫНДА АҚЫЛ ТӘРБИЯСЫ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (ILIM hám JÁMIYET, 2019)
The article is devoted to the study of issues of mental education in the folklore epos «Shariyar» on the basis of the analysis of the main hero Shariyar. The authors of the article has taken for the investigation two variants of the epos-of the famous Karakalpak jiraus-Oteniyaz and Kulamet-jirau.